National Referendums in Hungary and Albania: A Comparative Perspective - Pomarański, Marcin (What’s New in the New Europe? Redefining Culture, Politics, Identity, 2019)
The article is the result of research Project No. 2014/15/B/HS5/01866 founded by the National Science Centre.